Progic 2025: The 12th Workshop on Combining Probability and Logic: Carnegie Mellon University, Pittsburgh, PA — April 3–5, 2025 (The Reasoner, 2025)
Report on the Conference Progic 2025: The 12th Workshop on Combining Probability and Logic, Carnegie Mellon University, Pittsburgh, PA -- April 3–5, 2025.
Keywords: Probability; Logic